Acorn choice by small mammals in a Mediterranean deciduous oak forest. Issue 2 (4th March 2017) - Bonacchi, A.; Bartolommei, P.; Gasperini, S.; Manzo, E.; Cozzolino, R.
Abstract : Several studies regarding acorn choice by granivorous rodents have been conducted in dry Mediterranean oak forests, mainly composed by evergreen oaks. However, a lack of knowledge still persists about this subject in sub-Mediterranean forests dominated by deciduous oaks. We investigated the choice between Quercus cerris and Q. pubescens acorns by terrestrial small mammals in a deciduous oak forest of Central Italy, dominated by Q. cerris . Using a cafeteria-style feeding experiment, we tested 14 Apodemus flavicollis, and 10 Myodes glareolus . Animals were kept in outdoor experimental enclosures and given simultaneously a sample of acorns of the two oak species collected in situ. All seeds were sound and of the same size, shape and weight. Seed consumption was checked regularly, to record the percentage of consumed acorn sample. To evaluate a possible influence of pericarp on choice, acorns were presented both whole and shelled. Biochemical composition of seeds was analysed. Acorns of both oaks were similar in protein, lipid, carbohydrate and ash contents and energetic value, differing only in tannins and fibre content, with Q. pubescens having 51% less tannins and 35% less fibres than Q. cerris . The cafeteria experiments revealed a significant feeding preference by rodents for the less common Q. pubescens acorns, except for M. glareolus when presented with whole acorns. This overall preference, observed also at the individual level, could reflect a general foraging strategy aimed at maximising metabolisable energy and nutrients intake, avoiding anti-nutrients (i.e. tannins). To our knowledge, this is the first study on acorn choice by terrestrial rodents in sub-Mediterranean deciduous oak forests. Our findings not only provide information about the feeding behaviour of these species, but also may help future researchers to evaluate the role of these food resources in small mammal abundance, spatial distribution and population dynamics.